2018
DOI: 10.1007/s00572-018-0836-x
|View full text |Cite
|
Sign up to set email alerts
|

Current and potential distribution of the ectomycorrhizal fungus Suillus lakei ((Murrill) A.H. Sm. & Thiers) in its invasion range

Abstract: Suillus lakei is an ectomycorrhizal fungus native to North America and known in Europe, South America, and New Zealand. This contribution aims to illustrate the worldwide biogeography of S. lakei based on sporocarp records. Species distribution modeling was used to assess the suitable niche distribution of S. lakei, based on the climatic variables as well as distribution of its ectomycorrhizal partner, Douglas fir. In general, distribution of suitable niches of S. lakei greatly overlaps with the distribution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…2100-8200 (vs 2800-5800), and precipitation seasonality (bio15) values up to 80 mm (vs up to 40 mm). The current potential range of C. archeri in Europe is much broader than its actual occurrence as revealed by the occurrence data (Table 5), further confirming our previous studies showing that the realized niches of nonnative fungi are smaller than the predicted niches (Pietras et al 2018;Banasiak et al 2019;Pietras 2019;Pietras and Kolanowska 2019). Our model indicated that numerous suitable habitats are located in Europe, e.g., in the British Isles, Apennine Peninsula, Carpathians, Balkans, and Eastern Europe, where no GBIF records of the fungus are currently available (GBIF.org, 26 October 2018b).…”
Section: Where Did C Archeri Originate?supporting
confidence: 88%
See 3 more Smart Citations
“…2100-8200 (vs 2800-5800), and precipitation seasonality (bio15) values up to 80 mm (vs up to 40 mm). The current potential range of C. archeri in Europe is much broader than its actual occurrence as revealed by the occurrence data (Table 5), further confirming our previous studies showing that the realized niches of nonnative fungi are smaller than the predicted niches (Pietras et al 2018;Banasiak et al 2019;Pietras 2019;Pietras and Kolanowska 2019). Our model indicated that numerous suitable habitats are located in Europe, e.g., in the British Isles, Apennine Peninsula, Carpathians, Balkans, and Eastern Europe, where no GBIF records of the fungus are currently available (GBIF.org, 26 October 2018b).…”
Section: Where Did C Archeri Originate?supporting
confidence: 88%
“…Species distribution models are rather infrequently used in research on nonpathogenic fungi. Thus far, analyses of the future distributions of these organisms have been implemented in biogeographical studies on Boletales in North America (Pietras et al 2018;Banasiak et al 2019;Pietras 2019;Pietras and Kolanowska 2019) and on rare wood-inhabiting saprotrophs restricted to European boreal forests (Kujawska et al 2021). Therefore, studies of C. archeri and its introduction outside of its native range contribute to the discussion on the occurrence of nonpathogenic fungi outside their natural habitats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, there were also many species-specific environmental responses, as found for plants and animals, highlighting the need for more studies that attempt to link species responses to key life-history traits. In a recent study [44], the distribution of the ectomycorrhizal fungus Suillus lakei was found to be mainly impacted by the tree host distribution (Douglas fir) but they also observed that precipitation of the coldest quarters, isothermality and annual mean temperature were important factors influencing the potential distribution of S. lakei. This example suggests that biotic variables will be important to include when generating fungal SDMs ( figure 3).…”
Section: Diversity and Distributionmentioning
confidence: 97%